Anti-Semitism and Islamophobia in the Netherlands: concepts, developments, and backdrops - Vellenga, Sipco J. (Journal of contemporary religion, 2018)
In recent years, the Netherlands has been frequently confronted with public incidents of anti-Semitism and Islamophobia. After defining the complex concepts of anti-Semitism and Islamophobia, presenting the theoretical approach to these phenomena, and sketching the societal context in which they are embedded, this article describes the development of the numbers of reported expressions of anti-Semitism and Islamophobia in the Netherlands since the turn of the century. It notes that the general level of annual numbers of recorded incidents of the phenomena has increased since 2000 and, at the same time, there are significant fluctuations in the numbers of notified incidents per year. These fluctuations correlate to outbursts of violence in the Middle East and to acts of violence committed in the name of Islam in the West, while the general higher level of incidents of anti-Semitism and Islamophobia relates to numerous and various threats experienced in the context of the Dutch multi-ethnic society, changes in national identity, and trends in globalisation.